Analysis of Factors Affecting the Efficiency of Research and Innovation Activities of Higher Education Institutions - Raximova Dilnoza Davronovna (European Science Publishing, 2024)
This article explores the determinants of efficiency in research and innovation activities within higher education institutions, focusing on selected institutions in Uzbekistan. The study involves 502 professors and teachers from various institutions, analyzing factors such as funding sources, scientific personnel qualifications, collaboration networks, material and technical support, institutional backing, student involvement, and external infrastructure. Utilizing STATA 15.0 software, the econometric analysis employs the Ordinary Least Squares (OLS) regression model to investigate the impact of these factors on research and innovation performance. The study formulates and tests hypotheses related to financial support, personnel collaboration, industry partnerships, resource availability, institutional support, student engagement, and external infrastructure. The findings contribute to understanding the dynamics shaping the effectiveness of research and innovation activities in higher education institutions.
Keywords: Higher Education, Research and Innovation Efficiency, Funding, Scientific Personnel, Collaboration, Material and Technical Support, Institutional Support, Student Involvement, External Infrastructure, Uzbekistan.